Genome-Wide Identification of Powdery Mildew Resistance in Common Bean (Phaseolus vulgaris L.) - Binagwa, Papias H.; Traore, Sy M.; Egnin, Marceline; Bernard, Gregory C.; Ritte, Inocent; Mortley, Desmond; Kamfwa, Kelvin; He, Guohao; Bonsi, Conrad (Frontiers in Genetics, 2021)
Genome-wide association studies (GWAS) have been utilized to detect genetic variations related to several agronomic traits and disease resistance in common bean. However, its application in the powdery mildew (PM) disease to identify candidate genes and their location in the common bean genome has not been fully addressed. Single nucleotide polymorphism (SNP) genotyping with a BeadChip containing 5398 SNPs was used to detect genetic variations related to PM disease resistance in a panel of 211 genotypes grown under two field conditions for two consecutive years. Significant SNPs identified on chromosomes Pv04 and Pv10 were repeatable, ensuring the phenotypic data's reliability and the casual relationship. A cluster of resistance genes was revealed on the Pv04 of the common bean genome, coiled coil-nucleotide-binding site–leucine-rich repeat (CC-NBS-LRR, CNL), and Toll/interleukin-1 receptor-nucleotide-binding site–leucine-rich repeat type (TIR-NBS-LRR, TNL) like resistance genes were identified. Furthermore, two resistance genes, Phavu_010G1320001g and Phavu_010G136800g, were also identified on Pv10. Further sequence analysis showed that these genes were homologs to the disease resistance protein (RLM1A-like) and the putative disease resistance protein (At4g11170.1) in Arabidopsis. Significant SNPs related to two LRR receptor-like kinases (RLK) were only identified on Pv11 in 2018. Many genes encoding the auxin-responsive protein, TIFY10A protein, growth-regulating factor 5-like, ubiquitin-like protein, cell wall RBR3-like protein related to PM disease resistance were identified nearby significant SNPs. These results suggested that the resistance to PM pathogen involves a network of many genes constitutively co-expressed.